Effect of a combination of enzymes on the fundamental rheological behavior of bread dough enriched with resistant starch - Altuna, Luz (2016)
The effect of three enzymes on the fundamental rheological parameters of bread dough with high content of resistant starch (RS) was studied. The RS was added as an alternative to increase the fiber ingestion while the enzymes, to overcome the gluten dilution. Optimum dough was formulated with partial substitution of wheat flour by RS (12.5 g/100 g) and enzymes transglutaminase (4 mg/100 g), glucose oxidase (2.5 mg/100 g) and xylanase (0.5 mg/100 g). Dough produced with RS and without enzymes was considered as control and dough without RS or enzymes was considered as regular for comparison. Fundamental rheological parameters were obtained from uniaxial extension, biaxial extension and oscillatory tests. Also, starch gelatinization and retrogradation were studied by differential scanning calorimetry. The partial replacement of WF by RS resulted in less extensible dough, whereas the addition of enzymes increased the strain hardening index allowing higher dough expansion. The addition of enzymes reduced the elastic modulus resulting in a behavior similar to the regular dough. RS was not gelatinized during baking, hence it can be considered as dietetic fiber. Wheat starch retrogradation after 7 days of storage was observed, indicating bread aging.